Knowing how things might have been - Jago, Mark (Springer, 2018)
I know that I could have been where you are right now and that you could have been where I am right now, but that neither of us could have been turnips or natural numbers. This knowledge of metaphysical modality stands in need of explanation. I will offer an account based on our knowledge of the natures, or essences, of things. I will argue that essences need not be viewed as metaphysically bizarre entities; that we can conceptualise and refer to essences; and that we can gain knowledge of them. We can know about which properties are, and which properties are not, essential to a given entity. This knowledge of essence offers a route to knowledge of the ways those entities must be or could be.